1998
DOI: 10.1073/pnas.95.20.11915
|View full text |Cite
|
Sign up to set email alerts
|

Mouse embryonic stem cells carrying one or two defective Msh2 alleles respond abnormally to oxidative stress inflicted by low-level radiation

Abstract: Chronic oxidative stress may play a critical role in the pathogenesis of many human cancers. Here, we report that mouse embryonic stem (ES) cells deficient in DNA mismatch repair responded abnormally when exposed to low levels of ionizing radiation, a stress known to generate oxidative DNA damage. ES cells derived from mice carrying either one or two disrupted Msh2 alleles displayed an increased survival following protracted exposures to low-level ionizing radiation as compared with wild-type ES cells. The inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
108
1
1

Year Published

2000
2000
2008
2008

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(120 citation statements)
references
References 43 publications
7
108
1
1
Order By: Relevance
“…5,16 The observation that MMR-deficient human tumor cell lines and mouse embryonic fibroblasts (MEFs) were resistant to treatment with 6-thioguanine (6-TG), N-methyl-N'-nitro-N-nitrosoguanidine (MNNG), low levels of ionizing radiation (IR), as well as other nucleotide modifying agents raised the possibility that protection from damage-induced apoptosis provided a selective advantage for these cells. [17][18][19][20][21] In this model, genomic instability accelerated tumorigenesis, but was perhaps not the origin of it. Support for this notion has come from the observation that Msh6 -/-embryonic stem (ES) cells, but not Msh3 -/-ES cells displayed resistance to MNNG.…”
Section: Autosomal Dominant Cancer Predisposition Syndromesmentioning
confidence: 99%
“…5,16 The observation that MMR-deficient human tumor cell lines and mouse embryonic fibroblasts (MEFs) were resistant to treatment with 6-thioguanine (6-TG), N-methyl-N'-nitro-N-nitrosoguanidine (MNNG), low levels of ionizing radiation (IR), as well as other nucleotide modifying agents raised the possibility that protection from damage-induced apoptosis provided a selective advantage for these cells. [17][18][19][20][21] In this model, genomic instability accelerated tumorigenesis, but was perhaps not the origin of it. Support for this notion has come from the observation that Msh6 -/-embryonic stem (ES) cells, but not Msh3 -/-ES cells displayed resistance to MNNG.…”
Section: Autosomal Dominant Cancer Predisposition Syndromesmentioning
confidence: 99%
“…In addition to Myh and Ogg1, the mismatch repair gene products also prevent GO accumulation and its mutagenic effects in eukaryotes (15)(16)(17). Recognition and repair of either GO or A or both in GO:A mismatches during DNA replication may be an alternative means of minimizing the mutations caused by GO lesions.…”
Section: Introductionmentioning
confidence: 99%
“…This may be because of the lowered Msh2 gene dosage and the increased mutation load caused by higher GO accumulation. In support of this possibility, Msh2 gene dosage affects GO accumulation levels in both mouse embryonic fibroblasts and embryonic stem cells (16,17). Haploinsufficiency at tumor suppressor loci may result in a growth advantage and allow for the manifestation of neoplastic phenotypes after mutation of only a single allele (36).…”
mentioning
confidence: 95%
“…These include analyses of the level of DNA lesions and the apoptotic response following exposure to low level radiation treatment (DeWeese et al, 1998), and also by studies which have shown very low rates of LOH at the Msh2 locus in tumours arising in Msh2 hemizygotes (De Wind et al, 1998).…”
mentioning
confidence: 99%